Towards X‐ray in‐situ visualization of ammonothermal crystal growth of nitrides. Issue 9 (2nd May 2014) - Schimmel, Saskia; Künecke, Ulrike; Baser, Hasan; Steigerwald, Thomas G.; Hertweck, Benjamin; Alt, Nicolas S. A.; Schlücker, Eberhard; Schwieger, Wilhelm; Wellmann, Peter
Abstract In‐situ X‐ray visualization of hydrothermal growth of silicalite‐1 is applied as an intermediate step for developing X‐ray in‐situ visualization techniques for ammonothermal growth of nitride materials. In‐situ X‐ray imaging of silicalite‐1 crystals grown by the bulk material dissolution technique (Shimizu and Hamada, Angew. Chem., Int. Ed. 38, 2725 (1999) [1]) is demonstrated using a stainless steel autoclave equipped with ceramic aluminium oxide windows. Processes in the reaction medium such as local density changes are also visualized. The transferability of the technique to ammonothermal growth of nitrides is evaluated. Furthermore, the applicability of windowless autoclaves for X‐ray in‐situ monitoring of ammonothermal crystal growth of nitrides is investigated. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)